Effective Deep Brain Stimulation for Obsessive-Compulsive Disorder Requires Clinical Expertise - van Westen, Maarten; Rietveld, Erik; Denys, Damiaan (Frontiers in Psychology, 2019)
Background. Deep Brain Stimulation (DBS) is an innovative treatment for severe Obsessive-Compulsive Disorder (OCD). Electrodes implanted in specific brain areas allow clinicians to directly modulate neural activity. DBS affects symptomatology in a completely different way than established forms of treatment for OCD, such as psychotherapy or medication. Objective. To understand the process of improvement with DBS in patients with severe OCD. Methods. By means of open-ended interviews and participant observation we explore how expert clinicians involved in the post-operative process of DBS optimization evaluate DBS effects. Results. Evaluating DBS effect is an interactive and context-sensitive process which gradually unfolds over time and requires integration of different sources of knowledge. Clinicians direct DBS optimization towards a critical point where they sense that patients are being moved with regard to behaviour, emotion, and active engagement, opening up possibilities for additional Cognitive Behavioural Therapy (CBT). Discussion. Based on the theoretical framework of Radical Embodied Cognitive Science, we assume that clinical expertise manifests itself in the pattern of interaction between patient and clinician. To the expert clinician, this pattern reflects the patient’s openness to possibilities for action (‘affordances’) offered by their environment. OCD patients’ improvement with DBS can be understood as a change in openness to their environment. The threshold for patients to engage in activities is decreased and a broader range of daily life and therapeutic activities becomes attractive. Movement is improvement.